Pengembangan Media Membaca dan Menulis Permulaan untuk Siswa Kelas I Sekolah Dasar - Aprilia, Nia; Iswara, Prana Dwija; Gusrayani, Diah (Jurnal Pena Ilmiah, 2021)
The results of the needs analysis on the implementation of the student’s ability test showed that there were still students who had difficulty reading and writing at the beginning. This is caused by several factors, one of which is the use of methods and media that tend to be monotonous during the implementation of distance learning and also the limited sources of teaching materials used by teachers. From this background, a solution is needed so that students can continue to learn and improve their early reading and writing skills outside of school. Android-based learning applications are one of the solutions and the researchers are trying to develop in this research. The research method used is research and development (RD) with the ADDIE development model. The results of the study showed early reading and writing application had a feasibility percentage of 85% from material expert and 80% from media expert. After being declared eligible, this application is implemented to determine student responses as users. The results of the small-scale test showed that the application had a percentage of 82% (Very Feasible) and experienced an increase in the percentage in the large-scale test of 87% (Very Feasible).